Effectiveness of Ethnomathematics-Based Learning Media on Students' Understanding of Geometry Material Concepts in Grade IV - Utami, Nurul Fitria; Irawati, Ratna Kartika (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2024)
The mismatch between what students receive at school and outside school causes the majority of elementary school students to find mathematics difficult to understand. This research aims to determine differences in understanding of the concept of geometry material between classes that use ethnomathematics-based learning media and classes that do not use learning media as usual. This research uses a quantitative approach with experimental methods. The location of this research is at MI Al-Fitrah Tamiang Layang, Central Kalimantan. The sampling technique used is saturated sampling where all members of the population are used as research samples. Data collection techniques through test, observation and documentation. There are 2 data analysis techniques used, namely descriptive statistical analysis and statistical analysis. The findings show that the independents sample t-test with t count of 3.028 and a significance of 0.004 shows that H 0 is rejected and h a is accepted, which means there is a significant difference in understanding the concept of geometric materials between classes that use ethnomathematics-based learning media and those that do not use learning media. Apart from that, the average score for classes that use ethnomathematics-based learning media is higher than classes that do not use learning media, so it can be concluded that the use of ethnomathematics-based learning media is effective in learning mathematics, geometry material.